Evaluation of ELISA tests specific for Shiga toxin 1 and 2 in food and water samples. (July 2017) - Gehring, Andrew G.; Fratamico, Pina M.; Lee, Joseph; Ruth, Leah E.; He, Xiaohua; He, Yiping; Paoli, George C.; Stanker, Larry H.; Rubio, Fernando M.
Abstract: Two enzyme-linked immunosorbent assay (ELISA) kits were evaluated for their effectiveness in detecting and differentiating between Shiga toxin 1 and 2 (Stx1 and Stx2) produced by Shiga toxin-producing E. coli (STEC) inoculated into food and water samples. Each kit incorporated monoclonal antibodies previously determined to bind all known Stx1 or Stx2 subtypes with the exception of Stx2b. Four different sample types, including ground beef, Romaine lettuce, pond water, and pasteurized milk were inoculated with Stx1a-, Stx2a-, or Stx1a- and Stx2a-producing STEC strains, enriched using modified tryptic soy broth (containing mitomycin C) for 6, 16, and 22 h, and tested using the ELISA kits in the presence of a bacterial protein extraction reagent (B-PER™). The two Shiga toxin types were readily detected and distinguished for all tested sample types. There was good overall sensitivity, specificity, variance, and reproducibility for the two ELISA kits and they should prove useful for application in food testing. Highlights: Two new ELISA tests distinguished Stx1- from Stx2- producing Escherichia coli . ELISA tests employed antibodies that differentiated nine of ten Stx subtypes. ELISA tests demonstrated to be effective with select food and water samples.